Solid Solution of Bi and Sb for Robust Lithium Storage Enabled by Consecutive Alloying Reaction. Issue 38 (8th August 2021) - Wang, Yutao; Yu, Ruohan; Luo, Tingting; Ma, Ganggang; Hu, Guangwu; Lyu, Jiahui; Zhou, Liang; Wu, Jinsong
Abstract: Materials with alloying reactions have significant potential as electrodes for lithium‐ion batteries (LIBs) due to its high theoretical capacity and appropriate lithiation potentials. Nonetheless, their cycling performance is inferior due to violent volume expansion and severe pulverization of active materials. Herein, solid solution of Bi0.5 Sb0.5 encapsulated with carbon is discovered to enable consecutive alloying reactions with manageable volume change, suitable for developing LIBs with high capacity and robust cyclability. A Sb‐rich shell and Bi‐rich core structure is formed in cycling since the alloying reaction between Sb and Li occurs first, followed by the alloying reaction between Bi and Li. Such a consecutive alloying reaction obeying the thermodynamic path is experimentally realized by the carbon capsulation, which acts as a protecting solid layer to avoid polarized reactions occurred when exposed directly to liquid electrolyte. The LIBs using Bi0.5 Sb0.5 @carbon run on the consecutive alloying reactions exhibits high capacity, prolonged lifespan (489.4 mAh g −1 after 2000 cycles at 1 A g −1 ) and fast kinetic, while those using bare Bi0.5 Sb0.5 suffer from worsened kinetic and thus a poor cycling performance owning to the polarized reactions. The work paves a way of developing alloy electrodes for alkaline‐ion rechargeable batteries with potential industry applications. Abstract : Solid solution of Bi0.5 Sb0.5 encapsulated with N‐doped carbon (Bi0.5 Sb0.5 @NC) is suitable for developing LIBs with high capacity and robust cyclability, owing to the consecutive alloying reaction. A Sb‐rich shell and Bi‐rich core structure with manageable volume change is formed in the consecutive alloying reaction, since the reaction between Sb and Li occurs first, followed by the reaction between Bi and Li.